Scope and delimitation of the right to honor in legal entities in the criminal sphere (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The objective of this investigation was to analyze whether the right to honor was attributable to a legal entity in the criminal area. From this perspective, changes have been observed over time regarding the right to honor. The methodology used has been documentary analysis, with its sources being refereed articles, sentences and case studies, which allowed us to know the characteristics of the right to honor and assigned to natural persons, various legal entities, or indeterminate groups and the access of this right on the part of legal entities of public law to the administration of justice, which has addressed it to give greater relevance to a complex issue but that needs to be regulated.
Keywords: administration of justice; honor; legal persons; natural persons; sentences